Die kerk as kragsentrale vir die wêreld: Opmerkings oor die kerk se advies en dienswerk - Lategan, LOK (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
The church as powerstation for the world: Remarks on the church’s advice and service work. This article asks the question whether the church makes any difference to the world. The author argues that the church can be a powerstation for the world through the church’s advice and service. The purpose of this article is therefore to outline the role of the church in society through its (the church’s) advice and service. The author argues that since the church is the body of Christ it cannot isolate itself from society. The church has the responsibility to advise its community to the alternative of God’s kingdom. In addition, service to the kingdom of God is synonymous with the church. It is therefore obvious that both service and advice should be defined in Christ. Paragraph one outlines the reason why the church is part of the society. The second paragraph provides the focus for the article. The third paragraph gives historical reasons for the church’s involvement with society. Paragraph four and five debates the theological and Biblical foundations for the church’s service and advice. In paragraph six a modern day confession for the church’s advice and service is suggested.